Fully Online Multicommand Brain-Computer Interface with Visual Neurofeedback Using SSVEP Paradigm. (26th July 2007) - Martinez, Pablo; Bakardjian, Hovagim; Cichocki, Andrzej
Abstract : We propose a new multistage procedure for a real-time brain-machine/computer interface (BCI). The developed system allows a BCI user to navigate a small car (or any other object) on the computer screen in real time, in any of the four directions, and to stop it if necessary. Extensive experiments with five young healthy subjects confirmed the high performance of the proposed online BCI system. The modular structure, high speed, and the optimal frequency band characteristics of the BCI platform are features which allow an extension to a substantially higher number of commands in the near future.